HUBUNGAN PERAN KEHANGATAN KELUARGA DENGAN KEMAMPUAN KOMUNIKASI EFEKTIF SISWA KELAS XI SMKN 6 PADANG SEMESTER GENAP TAHUN AJARAN 2025/2026 - Zelianti, Imelda; Linda Fitria; Yuliawati Yunus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between family warmth and effective communication among eleventh grade students of SMK Negeri 6 Padang in the 2025/2026 academic year. The family plays a fundamental role in shaping adolescents’ emotional and social development. A warm family environment characterized by affection, support, attention, and open communication is believed to contribute positively to students’ interpersonal communication skills. This research employed a quantitative approach using a correlational design. The population consisted of all eleventh grade students, with 212 students selected through proportional random sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using Pearson Product Moment correlation. The results showed that family warmth was generally categorized as moderate to high, and students’ effective communication was categorized as good. However, correlation analysis indicated that the relationship between family warmth and effective communication was very low and statistically not significant (r = 0.177; sig. = 0.142 > 0.05). These findings imply that effective communication among students may be influenced by other factors beyond family warmth.